An analytical method with numerical results to be used in the design of optical slab waveguides for optical communication system applications - Aadel M. Alatwi; Ahmed Nabih Zaki Rashed (Institute of Advanced Engineering and Science, 2021)
This study develops an analytical method with numerical results for the design of optical slab waveguides for optical communication system applications. An optical slab waveguide structure made of silicon on silicon dioxide material is designed and analyzed. The effective index of the mode is studied against variations in the waveguide dimensions. Transmission and reflection coefficients are studied and compared to the wavelength and dimensions of the waveguide. Variations are sketched with the x-axis, in addition to the electric field intensity distribution and effective refractive index. Waveguide bending loss is also studied with waveguide thickness and length variations within three waveguide transmission windows of 850 nm, 1300 nm, and 1550 nm.